Students' Perception of Problems in Speaking English at a Vocational High School in Cirebon - Cindi Naeni; Fitri Aprianti; Ikariya Sugesti (National Conference on Language, Education, and Technology Proceeding, 2021)
This research is aimed at studying the student’s problems in speaking at 11th grade of vocational high school. The research object is only centered on the learning process, while the subject of this research is an English students' at the school. During the learning activities carried out in 2 observations and 4 meetings were conducted. Observe the students' of applying learning process in the speaking class. Data collection techniques include questionnaire and interviews. On the preliminary researcher observed the students' learning process and then proceeded to the next meeting. Based on the data obtained from the observation, it can be seen that there are still many students who have problems when learning to speak English in class. The results of the interview show that after distributing questionnaire, and conducting interview, the researcher found that the 11th grade had many problems on speaking. The main factors of students’ problems because the environmental factors which do not support them to use English in their daily communication. This factor also have a big effect for students that they lack of motivation and seldom to practice English.